The Dilemma of Maintaining Intact Forest Through Certification - Kleinschroth, Fritz; Rayden, Tim; Ghazoul, Jaboury (Frontiers in Forests and Global Change, 2019)
Intact forests are natural and often extensive forests free from apparent anthropogenic degradation. Intact forests have important intrinsic and societal values, making their protection a high conservation priority. They are, however, vulnerable to being lost and degraded due to high opportunity costs and a lack of positive incentives to their preservation. Market-based mechanisms, such as voluntary certification, might provide a means to conserve intact forests while maintaining income through sustainable forest uses. Yet possibilities to ensure strict protection of large areas of intact forests through certification remain limited as long as premiums from certification are bound to the units of forest products that are sold. We explore challenges for incorporating intact forests into certification processes, and of maintaining intact forests within forest management units. To circumvent these challenges, it might be necessary to create a form of compensation payment scheme to overcome the foregone costs of intact forest preservation. Alternatively, certification systems might need to consider permitting some degree of regulated extraction in exchange for recognition and implementation of stringent forest preservation. This will require a re-evaluation of the way intactness is treated within current certification standards and the requirements for forestry within intact forests. Eventually, intact forest conservation and socially and economically viable forest management can only be reconciled on the landscape scale.